A three-year prospective study of illness in professional soccer players - Orhant, E.; Carling, C.; Cox, A. (Research in Sports Medicine, 2010)
The aim of this study was to investigate rates and patterns of illness in professional soccer and their impact on playing resources. Illnesses were prospectively diagnosed over three seasons in first-team professional soccer players (n = 81) by the club's physician. A total of 203 illnesses were diagnosed with a mean of 2.5 ± 0.7 complaints per player per season. The majority of complaints were classed as upper respiratory (74.5%) and gastrointestinal illnesses (13.7%). Of all illness episodes, 19.7% required a lay-off (mean duration: 2.1 days). Per season, 0.3% ± 0.01 of all working days were lost due to illness; each player lost an average of 1.1 ± 0.1 working days and missed 0.1 ± 0.2 matches. Results from this study suggest that common infectious illnesses have little impact on player availability in professional soccer.